Factores psicosociales y estrés en los estudiantes de enfermería Huamachuco 2016 - Amador Romero, Digna Diana (2017)
Research quantitative, descriptive, correlational, cross-sectional, aimed to establish the relationship between psychosocial factors: self-esteem, level of family support, degree of teacher support with the level of stress in students of vocational school nursing at the National University of Trujillobased Huamachuco. the conceptual contributions on self-esteem Coopersmith (1990) and the stress of Ivancevich (1992) was taken into account. The sample consisted of 72 students. Instruments used: Questionnaire psychosocial factors and evaluative Stress Scale. For data analysis statistical test was applied chi square independence of criteria in the program SPPS version 23. The results showed: 23.6% of students have high self-esteem, 23% high average self-esteem, high degree of family support is 41.7%, the highest degree of teacher support is 38.9%. And the stress level found was 41.7% lower. When performing the test statistic it was found that there is significant relationship between psychosocial factors and stress level nursing student.